2022
DOI: 10.3389/fmicb.2022.944361
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions and Cross-Kingdom Host Gene Regulation of Small RNAs in Lactobacillus plantarum-Derived Extracellular Vesicles

Abstract: Extracellular vesicle-mediated transfer of microRNAs is a novel mode of cell-to-cell genetic transmission. Extracellular vesicles produced by microbes have been shown to contain significant quantities of physiologically active molecules such as proteins, lipids, and RNA, which could be transported to host cells and play a key role in both inter-kingdom signaling and physiological responses. In this study, we identified sRNAs by sequencing small RNAs (sRNAs) from Lactobacillus plantarum-derived extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The copyright holder for this preprint this version posted May 7, 2024. ; https://doi.org/10.1101/2024.05.07.592932 doi: bioRxiv preprint However, also the release via membrane vesicles could be an explanation which is supported by vesicle releasing L. plantarum (Yu et al 2022). Interestingly, systematic analysis of the signal peptides and culture filtrates of different lactobacilli suggested that further bacterial species from the genera Lactobacillus, Akkermansia, and Enterococcus with described probiotic potential (Li et al 2024;Im et al 2023) release putative FPR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted May 7, 2024. ; https://doi.org/10.1101/2024.05.07.592932 doi: bioRxiv preprint However, also the release via membrane vesicles could be an explanation which is supported by vesicle releasing L. plantarum (Yu et al 2022). Interestingly, systematic analysis of the signal peptides and culture filtrates of different lactobacilli suggested that further bacterial species from the genera Lactobacillus, Akkermansia, and Enterococcus with described probiotic potential (Li et al 2024;Im et al 2023) release putative FPR2 ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular MVs have been described in both Gram-negative and Gram-positive bacteria, archaea and eukaryotes, and numerous reports have suggested that they serve various functional roles in for example cell-cell communication processes, host adaptation and antimicrobial defense by mediating the transfer of RNA, proteins and metabolites across cell boundaries (Brown et al 2015 , Liu et al 2018 , Gill et al 2019 , Yu et al 2022 ). An alternative hypothesis, particularly for eukaryotic MVs, is that their basic function is to secrete material out from the cell for off-site degradation and recycling of membrane molecules (Vidal 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the secreted RNA molecules mediate bacterial interactions with the host, such as for example serving host immunomodulatory functions (Tsatsaronis et al 2018 , Rodriguez and Kuehn 2020 , Kurata et al 2022 ). While small, non-coding RNAs have been directly associated with immunomodulatory responses (Koeppen et al 2016 , Yu et al 2022 , Sahr et al 2022 ), the specificity of such effects by bulk-RNA are not fully resolved. Furthermore, previous studies have shown that RNAs are secreted as fragments, arguing against a biological role for the large majority of secreted RNA molecules derived from long mRNA molecules (Rodriguez and Kuehn 2020 , Luz et al 2021 , Kurata et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a highly expressed sequence (sRNA71) was identified in Exosomes which were isolated from the culture supernatant of L. plantarum WCFS1 using ultracentrifugation. sRNA71 substantially reduced Tp53 expression in HEK293T cells and suppressed the gene expression through binding to the 3′UTR of Tp53 mRNA ( Yu et al, 2022 ). These exosomes contain bioactive substances that regulate the intestinal microbiome, such as extracellular enzymes, antibiotics, antimicrobials, antibiotic enzymes, iron carrier proteins, β-glucan, siRNA and polysaccharides, which can impact the type and quantity of intestinal flora, improve the growth and metabolism of probiotics in the intestine, and maintain intestinal health ( Uddin et al, 2020 ; Díaz-Garrido et al, 2021 ; Yang Z. et al, 2022 ).…”
Section: Structure and Function Of Lactobacillus-derived Exosomesmentioning
confidence: 99%